Chile : A Strategy to Promote Innovative Small and Medium Enterprises - World Bank (Washington, DC, 2013)
This study is to provide the Government of Chile with a review of the portfolio of small and medium enterprise (SMEs) development programs and the institutions that provide them, leading to recommendations to improve the effectiveness of a streamlined portfolio. This emphasis is important for economic reasons, given the sectors role in employment, and the possibility of improving its integration into the national economy and export-oriented production and marketing chains. However, this analysis also identifies areas where SMEs can more effectively leverage government programs to become more productive, efficient, and innovative. The analysis is based on interviews with key policymakers, managers and other staff of the government institutions responsible for most of the programs secondary reports, and discussions with small business managers, business association leaders, academicians and financial intermediaries. The report is organized as follows: The first chapter reviews the evolution of the macroeconomic and business environment in Chile, and provides the theoretical arguments upon which the governments intervention in favor of SMEs has been based; second chapter examines the characteristics of the SME sector, as well as key determinants of SME productivity and growth; third chapter describes the obstacles to SME development, such as constraints to financial resources; fourth chapter recommends a streamlined portfolio of private sector assistance projects and provides an institutional analysis of Production Development Corporation (Corporacion de Fomento de la Produccion) (CORFO), Agricultural Development Institute (Instituto de Desarrollo Agropecuario) (INDAP) and Technical Cooperation Service of Chile (Servicio de Cooperacion Tecnica de Chile) (SERCOTEC); fifth chapter focuses on programs that promote innovation, technology and networks, and finally sixth chapter offers strategic and operational recommendations to improve the effectiveness of the Governments investment in SME programs.